Phenotypic and genotypic characterization of Candida parapsilosis complex isolates from a Lebanese hospital - El Hady, Reine; Fattouh, Nour; Finianos, Marc; Bitar, Ibrahim; Fakih, Tarek; Husni, Rola; Khalaf, Roy A (Scientific reports, 2025)
The opportunistic pathogen Candida parapsilosis is a major causative agent of candidiasis leading to death in immunocompromised individuals. Azoles are the first line of defense in their treatment. The purpose of this study was to characterize eight fluconazole-resistant and sensitive C. parapsilosis hospital isolates through a battery of phenotypic tests that target pathogenicity attributes such as virulence, biofilm formation, stress resistance, and ergosterol content. Whole genome sequencing was carried out to identify mutations in key pathogenicity and resistance genes. Phylogenetic comparison was performed to determine strain relatedness and clonality. Genomic data and phylogenetic analysis revealed that two isolates were C. orthopsilosis and C. metapsilosis misidentified as C. parapsilosis. Whole genome sequencing analysis revealed known and novel mutations in key drug resistance and pathogenicity genes such as ALS6, ALS7, SAPP3, SAP7, SAP9, CDR1, ERG6, ERG11 and UPC2. Phylogenetic analysis revealed a high degree of relatedness and clonality within our C. parapsilosis isolates. Our results showed that resistant isolates exhibited an increase in biofilm content compared to the sensitive isolates. In conclusion, our study is the first of its kind in Lebanon to describe phenotypic and genotypic characteristics of nosocomial C. parapsilosis complex isolates having a remarkable ability to form biofilms.
Keywords: Biofilms; Hospitals; nemocnice; Antifungal Agents; sekvenování celého genomu; Fluconazole; fylogeneze; Humans; Lebanon; fungální léková rezistence; Whole Genome Sequencing; Phenotype; biofilmy; Phylogeny; Candidiasis; Microbial Sensitivity Tests; lidé; fenotyp; Drug Resistance, Fungal; infekce spojené se zdravotní péčí; Libanon; antifungální látky; flukonazol; kandidóza; genotyp; mikrobiální testy citlivosti; Candida parapsilosis; Cross Infection; Genotype